Biodiversity modelling reveals a significant gap between diversity hotspots and protected areas for Iranian reptiles. (18th November 2021) - Noori, Sajad; Hawlitschek, Oliver; Oldeland, Jens; Rajaei, Hossein; Husemann, Martin; Simões, Marianna
Abstract: The global struggle to conserve as many species as possible with limited resources requires an improvement of our knowledge on the distribution of biodiversity. In Iran, the state of knowledge is poor for most groups of organisms, except few vertebrate groups and vascular plants. Reptiles are one of the best known, most diverse vertebrate groups in Iran, with a high rate of endemism (ca. 29%), but distribution patterns and related environmental drivers remain poorly understood. In the present study, based on a large publicly available dataset, we use general additive modelling (GAM) to identify explanatory variables for species richness of reptiles in Iran. Results indicate heterogeneity parameters (range +entropy) as the variables with the highest explanatory values. Based on the grid cells of the predicted environmental richness, using hotspot analysis, we suggest seven hotspots of reptile diversity (HRDs) across the country. Our results corroborate the previously recognized HRDs and detect three additional ones, located alongside the major mountain ranges around the central deserts plateau, particularly in the Zagros Mountains. Four of the largest HRDs (ca. 90%) situate within the Irano‐Anatolian and Caucasus global biodiversity hotspot. In addition, our results reveal a large gap between identified HRDs and the current network of protected areas (PAs) in the country. While three of the detected HRDs in this study are partially touched (ca. 18%) by the PA network, overall, these areas are only covered by less than 10%. Therefore, the effectiveness of the current PAs for the protection of the reptile diversity of Iran is questionable. Abstract : Despite showing high endemism and diversity within Iran, distribution patterns of reptiles within the country remain poorly understood. Model selection on generalized additive models (GAMs) show that heterogeneity parameters (range +entropy) produce the best model explaining species richness and hotspots of reptile diversity (HRD: A–G). Furthermore, a hotspot analysis recover seven HRDs, but a gap analysis reveals large mismatch between HRDs and network of protected areas.